The need for a tailored national dementia plan in Ethiopia: A call for action - Ayele, Biniyam A.; Ali, Seid; Anbessie, Mohammed; Zewde, Yared Z.; Yoseph, Selam; Lee, Suzee; Valcour, Victor; Miller, Bruce (Frontiers in Neurology, 2023)
Globally, a rapid demographic transition is occurring with a significant increment in the proportion of older individuals. For the first time in history, individuals aged 65 and above outnumber that of children under 5 years of age. In Ethiopia, the life expectancy has shown dramatic improvements in the past few decades and is expected to reach 74 years by mid-century. Older age is considered the most important non-modifiable risk factor for dementia. Likewise, other modifiable diseases such as infectious diseases, non-communicable diseases, particularly cardiovascular diseases, and traumatic brain injuries are associated with dementia. Despite, the high prevalence of dementia risk factors and impending economic and health impact from dementia, no country in the sub-Saharan Africa (SSA), including Ethiopia, has developed a standalone or an integrated national dementia strategic plan to guide the overall effort to improve dementia care in the country. It is vital to design and develop a national dementia plan in line with a framework outlined by the 2017 World Health Organization (WHO) global action plan. The health, social, and economic burden from dementia is expected to be high to the developing countries such as Ethiopia unless clear prevention and management strategies are designed at a national level to cascade the care to the primary care level. The planned strategic policy may focus on improving the knowledge and skills of health care professionals. Translation and cultural adaptation of cognitive, functional, and behavioral assessment batteries is of paramount importance in improving the diagnostic accuracy along with availability of advanced imaging, biomarkers, and dementia treatment.